UUM mulls more PhD lecturers - Daily Express, (KK) (Daily Ekspress (kk), 2013)
SINTOK: Univarsiti Utara Malaysia (UUM) aims to have 851 lecturers with Doctorate of Philosophy (PhD) by 2015 to enable it to qualify as a research university with an autonomous status.